Religion, philosophy, and nationalism across the Middle East - Griffiths, Katie (New York Cavendish Square Publishing, 2017)
Explores religion, philosophy, and nationalism in Middle Eastern countries such as Egypt, Saudi Arabia, and Morocco.
The history of religion, philosophy, and nationalism across the Middle East -- Modern-day religion, philosophy, and nationalism in the Gulf region of the Middle East -- Modern-day religion, philosophy, and nationalism in the levant region of the Middle East -- Modern-day religion, philosophy, and nationalism in north Africa -- Important figures in religion, philosophy, and nationalism across the Middle East.
Includes bibliographical references and index.
14 - 17 years
108240
Keywords: Philosophy -- Middle East; Nationalism -- Middle East; Religion; Middle East -- Religion. -- Juvenile literature; Nonfiction